2014
DOI: 10.1097/meg.0000000000000147
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis

Abstract: Background The burden of hepatitis C virus genotype 4 (HCV-4) is high in Africa and East Mediterranean countries. Previous reports estimate sustained virologic response (SVR) rates in HCV-4 to be ~20–70%. However, many of these studies are limited by different study designs and small sample sizes. Aim Our aim was to evaluate treatment outcome and host/viral factors on SVR in HCV-4 patients treated with pegylated interferon and ribavirin (PEG IFN+RBV) in a systematic and quantitative fashion. Methods A comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 95 publications
(245 reference statements)
1
6
0
Order By: Relevance
“…Also, a previous meta-analysis on HCV-4 reported an association with SVR with favorable IL28B polymorphisms (rs12979860 CC and rs8099917 TT genotypes) [11]. The 2 studies on IL28B in our subgroup analyses showed a favorable association between SVR and rs8099917 TT genotype versus GT/GG (p = 0.014, OR: 15.0, 95% CI: 2.0-112.1) [21].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Also, a previous meta-analysis on HCV-4 reported an association with SVR with favorable IL28B polymorphisms (rs12979860 CC and rs8099917 TT genotypes) [11]. The 2 studies on IL28B in our subgroup analyses showed a favorable association between SVR and rs8099917 TT genotype versus GT/GG (p = 0.014, OR: 15.0, 95% CI: 2.0-112.1) [21].…”
Section: Discussionmentioning
confidence: 69%
“…Except for a previous study about HCV-4 [11], this is the first systematic review and meta-analysis to evaluate the influence of host and viral factors in patients with chronic HCV-6 treated with PEG-IFN+RBV. In our analysis, which included 14 studies comprising a total of 819 HCV-6 patients treated with PEG-IFN+RBV, the pooled SVR rate was 79.8% (95% CI: 0.77-0.83).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline patient characteristics, treatment protocol, and treatment responses of each study were recorded, including age, sex, prior relapser versus non-responder, treatment duration, rapid virological response (RVR), early virological response (EVR), and SVR. The extraction form initially contained a number of possible prognosticators of treatment success, as discussed by Yee et al , 3 but were removed after their omission from most articles we reviewed in-depth. Data extractions were performed by two authors (BZ and BEY).…”
Section: Methodsmentioning
confidence: 99%
“…2 Treatment success using pegylated interferon and ribavirin (P/R), defined by achieving sustained virological response (SVR), is estimated at 53% for treatment-naïve patients with HCV-4 infection. 3 This means that approximately half of the patients who undergo such regimen experience failure due to null-response or relapse. While newer direct-acting antiviral (DAA) medications have demonstrated remarkable efficacy in patients with HCV-1 infection who had experienced prior failure with P/R, 4 their cost and accessibility pose barriers to rapid worldwide adoption.…”
Section: Introductionmentioning
confidence: 99%